(untitled) (Journal of Parents and Teachers, 2017)
The world we live in is crying out for a change, an opportunity. We the teachers are the lucky ones for being able to do something in this matter. This article tries to give some light and show from the simplest experience the improvements in real contexts. It is our best moment. Don’t let it go. The time is ripe for quality teaching.